Evaluation of UT/LS hygrometer accuracy by intercomparison during the NASA MACPEX mission. Issue 4 (25th February 2014) - Rollins, A. W.; Thornberry, T. D.; Gao, R. S.; Smith, J. B.; Sayres, D. S.; Sargent, M. R.; Schiller, C.; Krämer, M.; Spelten, N.; Hurst, D. F.; Jordan, A. F.; Hall, E. G.; et al.
Abstract Acquiring accurate measurements of water vapor at the low mixing ratios (< 10 ppm) encountered in the upper troposphere and lower stratosphere (UT/LS) has proven to be a significant analytical challenge evidenced by persistent disagreements between high‐precision hygrometers. These disagreements have caused uncertainties in the description of the physical processes controlling dehydration of air in the tropical tropopause layer and entry of water into the stratosphere and have hindered validation of satellite water vapor retrievals. A 2011 airborne intercomparison of a large group of in situ hygrometers onboard the NASA WB‐57F high‐altitude research aircraft and balloons has provided an excellent opportunity to evaluate progress in the scientific community toward improved measurement agreement. In this work we intercompare the measurements from the Midlatitude Airborne Cirrus Properties Experiment (MACPEX) and discuss the quality of agreement. Differences between values reported by the instruments were reduced in comparison to some prior campaigns but were nonnegligible and on the order of 20% (0.8 ppm). Our analysis suggests that unrecognized errors in the quantification of instrumental background for some or all of the hygrometers are a likely cause. Until these errors are understood, differences at this level will continue to somewhat limit our understanding of cirrus microphysical processes and dehydration in the tropical tropopause layer.